2017
DOI: 10.1080/03079457.2017.1311006
|View full text |Cite
|
Sign up to set email alerts
|

The first whole genome sequence and pathogenicity characterization of a fowl adenovirus 4 isolated from ducks associated with inclusion body hepatitis and hydropericardium syndrome

Abstract: In June 2015, an infectious disease with high prevalence causing severe hydropericardium syndrome (HPS) first appeared in duck farms of northeast China. The disease showed high morbidity of 35% and mortality of 15% in a commercial duck farm with 200,000 45-day-old ducks. One strain of hypervirulent fowl adenovirus serotype 4 was identified and designated as HLJDAd15. The whole genome of the duck isolate was sequenced and found to contain the same large deletions as a genotype that has become prevalent in chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…HHS appears with high frequency in chickens, particularly in broilers, with a mortality that ranges from 10 to 100% (Vera-Hernández et al, 2016; Pan et al, in press). However, the disease has rarely emerged in other hosts with severe clinical signs and high mortality.…”
Section: Introductionmentioning
confidence: 99%
“…HHS appears with high frequency in chickens, particularly in broilers, with a mortality that ranges from 10 to 100% (Vera-Hernández et al, 2016; Pan et al, in press). However, the disease has rarely emerged in other hosts with severe clinical signs and high mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of the hexon sequence between the novel genotype FAdV-4 and each of the other FAdV-4 strains and other species of FAdVs was varied from 98.6–100% and 50.1–76.2%, respectively. The complete genome sequences of HLJFAd15 from layers and HLJDAd15 from ducks (identified as the novel genotype FAdV-4) were submitted to GenBank during our previous study [ 17 , 18 ]. The large genomic deletion 1966Del, located between ORF42 and 43, was sequenced and its absence confirmed in all of the other 15 clinical strains from chickens with emerged HHS, but did not appear in KR5 (HE608152) and ON1 (GU188428) isolated outside of China.…”
Section: Resultsmentioning
confidence: 99%
“…KU991797) and HLJDAd15 (GenBank no. KX538980) were isolated from layers and ducks, respectively, in our previous studies and shown to be highly virulent strains [ 17 , 18 ]. The remaining 15 clinical isolates were all from chickens with severe HHS from different provinces in China ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations